2016
DOI: 10.1038/ng.3522
|View full text |Cite
|
Sign up to set email alerts
|

Active DNA demethylation at enhancers during the vertebrate phylotypic period

Abstract: The vertebrate body plan and organs are shaped during a conserved embryonic phase called the phylotypic stage. However, the mechanisms that guide the epigenome through this transition and their evolutionary conservation remain elusive. Here we report widespread DNA demethylation of enhancers during the phylotypic period in zebrafish, Xenopus tropicalis and mouse. These enhancers are linked to developmental genes that display coordinated transcriptional and epigenomic changes in the diverse vertebrates during e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
231
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(258 citation statements)
references
References 80 publications
27
231
0
Order By: Relevance
“…Recently, it has been demonstrated that binding sites for the tomato ripening inhibitor transcription factors were commonly localized in hypomethylated regions of the promoters of ripening-associated genes whose expression was increased concurrently with gradual deceases in DNA methylation (Zhong et al, 2013). Also, we do not rule out the possibility that, in some cases, binding of transcription factors to specific promoter regions may lead to active demethylation of these regions, as recently demonstrated in other systems (Stadler et al, 2011;Pacis et al, 2015;Bogdanovi c et al, 2016). In other words, DNA hypomethylation in some cases could be the consequence of gene up-regulation and not the cause.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, it has been demonstrated that binding sites for the tomato ripening inhibitor transcription factors were commonly localized in hypomethylated regions of the promoters of ripening-associated genes whose expression was increased concurrently with gradual deceases in DNA methylation (Zhong et al, 2013). Also, we do not rule out the possibility that, in some cases, binding of transcription factors to specific promoter regions may lead to active demethylation of these regions, as recently demonstrated in other systems (Stadler et al, 2011;Pacis et al, 2015;Bogdanovi c et al, 2016). In other words, DNA hypomethylation in some cases could be the consequence of gene up-regulation and not the cause.…”
Section: Discussionmentioning
confidence: 89%
“…Our understanding of the effect of TET2 mutations thus remains incomplete. It has been shown, however, that in embryonic stem cells, Tet2 single [41] and Tet1/2/3 triple [42] knockout results in hypermethylation at selected enhancer regions.…”
Section: Epigenetic Abnormalities Caused By Tet2 Mutationsmentioning
confidence: 99%
“…Despite recent evidence for attenuation of polymerase II transcription elongation by 5caC [19], the functional role of these later 5mC oxidation products still remains to be fully understood. Genome-wide mapping in a variety of tissues and cell types at different developmental time points suggest a role of 5hmC in DNA loss of CpG methylation at specific regulatory elements, namely enhancers [2024]. Yet, only one report assessed 5hmC at more than one single time point during brain development in the mouse.…”
Section: Introductionmentioning
confidence: 99%
“…Besides its role as an intermediate in DNA loss of CpG methylation, 5hmC may also be an epigenetic mark with own regulatory functions. 5hmC was shown to be predominantly stable in various genomic contexts [23, 2527] and to have its own reader proteins [20, 2830]. In addition to enhancers [22, 26, 3136], 5hmC was found to be enriched within gene bodies [22, 26, 32, 34, 35, 37].…”
Section: Introductionmentioning
confidence: 99%